Marathon Run I: Effects on Blood Coagulation and Fibrinolysis - Mandalaki, T; Dessypris, A; Louizou, C; Bossinakou, I; Panayotopoulou, C; Antonopoulou, A (Thrombosis and Haemostasis, 1977)
Blood coagulation and fibrinolysis were assessed in 13 Finnish amateur runners aged 31 to 48, and one 65-year old taking part in a non-competitive marathon (42.2 km). After the run the mean values of partial thromboplastin time showed a very significant shortening, whereas the mean values of the prothrombin time and of plasma fibrinogen were not significantly altered. The mean values of euglobulin lysis time were significantly shorter and the mean values of fibrin degradation products increased highly significantly. After the run, protamine sulphate was positive or strongly positive in all subjects, whereas the ethanol gelation test was negative in all runners; no cryofibrinogen was detected in any participant. Thus, running a marathon race affects the haemostatic balance and activates the fibrinolytic mechanism. The effects of training and physical fitness on the above parameters are discussed.